THE ROLE OF STORYTELLING IN DEVELOPING CHILDREN’S LANGUAGE SKILLS - Utesinova Aygul Samat qizi; Kenjebaeva Shaxnoza Muratbay qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Introduction. The main goal of language teaching is to develop learners into individuals who can communicate freely in real-life situations, professional environments, and social contexts. However, in many educational systems, including schools and higher educational institutions in Uzbekistan, speaking skills often remain secondary compared to grammar or writing skills. This issue is largely connected to the quality and quantity of classroom interaction organized within the learning environment. A classroom is not merely a place where information is delivered; rather, it is a dynamic environment where learners actively use language, make mistakes, receive corrections, and learn through practice. The interaction that takes place in this environment between teacher and students, among students themselves, and between students and texts or tasks becomes a key tool in developing speaking skills. This thesis examines the role of classroom interaction in improving speaking abilities from the perspectives of theoretical foundations, empirical research, and practical recommendations.